Supporting pupils’ mental health in schools. Teaching staff’s and school nurses’ perceptions and the suitability of a webbased support system for pupils - Markkanen, Pihla (fi=Turun yliopisto|en=University of Turku|, 2021)
School is an essential part of pupils’ lives, and teaching staff and school nurses have an important role in supporting pupils’ mental health. The aim of this study was to enhance knowledge related to supporting pupils’ mental health in schools. The study has three phases, and a multi-methods approach was used. In Phase I, teaching staff’s perceptions of pupils’ mental health and capacities to support it were studied. First, focus group interviews with teaching staff (N=16) were conducted. The data were analysed with inductive content analysis. Second, during an eLearning course, participants (N=8) submitted reflective writings about the challenging situations they had experienced with pupils. These writings were analysed with a combination of deductive and inductive content analysis. In Phase II, school nurses’ (N=167) perceptions of pupils’ mental health and their capacities to support it were studied. A national survey with structured questionnaires and open-ended questions for school nurses was conducted. The quantitative data were analysed using descriptive statistics and the qualitative data with manifest content analysis. In Phase III, the web-based support system (Depis.Net), originally developed for adolescents with symptoms of depression, was evaluated as a universal school-based mental health intervention among 21 adolescents. The quantitative data were analysed with descriptive statistics, and the qualitative data were analysed with deductive content analysis. The results of this study show that, in terms of pupils’ mental health, teaching staff are mainly concerned with challenging situations with pupils and how pupils with mental health problems should be supported. School nurses have capacities to support the mental health of pupils, but they desire more training on interventions. The web-based support system was found to be suitable as a universal mental health intervention in a school environment. Pupils used the web-based support system actively and gave positive feedback on it. Moreover, it was helpful in identifying pupils with needs for mental health support. The capacity of teachers and school nurses to support pupils’ mental health should be enhanced through offered training and the implementation of mental health interventions in schools. These measures would support pupils’ mental health and the early recognition of mental health problems in schools. Web-based support systems may be useful interventions for mental health support in schools.

Oppilaiden mielenterveyden tukeminen kouluissa - Opetushenkilöstön ja kouluterveydenhoitajien näkemyksiä sekä verkkopohjaisen mielenterveyden tukiohjelman soveltuvuus oppilaille Koulu on merkittävä osa lasten ja nuorten elämää ja opetushenkilöstöllä ja kouluterveydenhoitajilla on tärkeä rooli oppilaiden mielenterveyden tukemisessa. Tutkimuksen tavoitteena oli saada tietoa oppilaiden mielenterveyden tukemisesta kouluissa. Tutkimus oli monimenetelmätutkimus, joka toteutettiin kolmessa vaiheessa. Vaiheessa I tutkittiin opetushenkilöstön näkemyksiä ja valmiuksia oppilaiden mielenterveyden tukemiseen. Aluksi tutkimusaineisto kerättiin opetushenkilöstön (N=16) ryhmähaastatteluiden avulla ja analysoitiin induktiivisen sisällönanalyysin avulla. Myöhemmin opetushenkilöstö (N=8) kirjoitti osana verkkokurssia, reflektiivisiä kirjoitelmia kokemistaan haastavista tilanteista oppilaiden kanssa. Kirjoitelmat analysoitiin deduktiivis-induktiivisella sisällön analyysillä. Vaiheessa II kouluterveydenhoitajien (N=167) näkemyksiä ja valmiuksia oppilaiden mielenterveyden tukemiseen tutkittiin kansallisessa kyselytutkimuksessa, joka sisälsi strukturoituja ja avoimia kysymyksiä. Määrällinen aineisto analysoitiin kuvailevin tilastollisin menetelmin ja laadullinen aineisto analysoitiin sisällön analyysin avulla. Vaiheessa III alun perin masennusoireista kärsiville nuorille kehitettyä tukiohjelmaa (Depis.Net) testattiin kouluympäristössä 21 nuoren kanssa. Määrällinen aineisto analysoitiin kuvailevin tilastollisin menetelmin ja laadullinen deduktiivisen sisällön analyysin avulla. Tutkimuksen tulokset osoittavat, että opetushenkilöstön pääasialliset huolet oppilaiden mielenterveydestä liittyivät haastaviin tilanteisiin oppilaiden kanssa sekä siihen, miten mielenterveysongelmista kärsiviä oppilaita tulisi tukea. Koulunterveydenhoitajilla on valmiuksia oppilaiden mielenterveyden tukemiseen, mutta he toivoivat lisäkoulutusta interventioista. Verkkopohjainen tukiohjelma oli soveltuva käytettäväksi mielenterveysinterventiona kouluympäristössä. Oppilaat käyttivät tukiohjelmaa aktiivisesti ja antoivat siitä positiivista palautetta. Lisäksi se auttoi tunnistamaan oppilaita, joilla oli tarvetta mielenterveyden tuelle. Opetushenkilöstön ja kouluterveydenhoitajien valmiuksia oppilaiden mielenterveyden tukemiseen tulisi vahvistaa tarjoamalla heille koulutusta ja mielenterveysinterventioita käyttöön. Tämä tukisi oppilaiden mielenterveyttä sekä mielenterveys ongelmien varhaista tunnistamista kouluissa. Verkkopohjaiset tukiohjelmat voivat olla hyödyllisiä oppilaiden mielenterveyden tukemisessa.